Development Of Colored Flour Plasticine Educational Game Tools (Ape) To Improve Early Childhood Creativity At Kejora Paud In The 2024/2025 Academic Year - Fatwaturrahimi, Nika; Ramzi, Muhajirin; Rahayu, Fitriani (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to develop Color Flour Plasticine educational game tools in increasing children's creativity. The focus of this research are: 1) Describing the Characteristics of Colored Flour Plasticine Educational Game Tools in Improving Early Childhood Creativity. 2) Analyzing the Development Process of Colored Flour Plasticine Educational Game Tools in increasing Children's Creativity. 3) Knowing how the effect of using educational game tools of color flour plasticine on increasing the creativity of early childhood. 4) Describing the advantages and disadvantages of the Color Flour Plasticine Educational Game Tool in increasing Early Childhood Creativity at Kejora Early Childhood Education for the 2024/2025 school year.Based on a comprehensive analysis of the characteristics, development process, effects, and advantages and disadvantages of color flour plasticine APE at Kejora Early Childhood Education, it can be concluded that this media is an educational game tool that is effective in increasing the creativity of children aged 4-5 years. This plasticine meets the ideal criteria of Educational Game Tools with the characteristics of raw material safety, education, and has a soft texture and attractive color variations. Although it has limitations in durability and texture stability, its systematic development process through expert validation and field trials showed a significant increase in children's creativity (post-t score). Technical weaknesses can be overcome through proper storage and teacher assistance, so this APE is still recommended as an innovative solution for early childhood education with limited budgets that prioritize creative and child-friendly learning.